CFD Analysis for Rigid Moving Body at the High Tidal Environment of Sea-bed - Md. Moktadir, Alam; Addie Irawan, Hashim (2014)
In this paper, the basic hydrodynamic theories have been used to find the hydrodynamic factors for the underwater moving rectangular body as considered the shape of underwater walking robot. The added-mass, wave drag and lift coefficients are determined using a frequency-domain, simple-source based boundary integral method. In this paper, the hydrodynamics added mass and drag forces will be determined theoretically calculation the Reynolds number is measured in order to understand the type of water flow over the structure. The relative velocity vectors, Reynolds number, drag and lift forces for each state of motion is obtained in both static water condition and in ocean current condition. Results are obtained for a range of wave frequencies and depths of the underwater robotic body submerged all for a fixed water depth of 50-100 m. With the wave exciting force and moment determined using the Navier-Stokes theory. The computational study is to determine body-shape effects on the incident and radiated wave forces and subsequently the motion response. This study and results further implemented to modern adaptive drag force model-based controller in horizontal flow disturbance control for underwater multilegged or wheeled robot.